Placement Sensor Modification of Photo Interrupter and ATDC Sensor on the Minolta Bizhub-421 Photocopy Machine - Imnadir Imnadir; Rudi Z.A; Abdul Khair Junaidi; M Dalil (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
Minolta photocopiers produce very good and reliable photocopier quality during their lifetime with the condition that the toner must be replaced with the original. If it is replaced by refilling, then refilling can only be done an average of three times. Meanwhile, replacement by refilling is needed by small and medium business units (SMEs) in an effort to save costs. Recharging that exceeds the average three times will cause the Minolta photocopier to have an error with code C032. Therefore, this paper was conducted to increase the frequency of the toner refill process as a solution for the Minolta Bizhub 421 machine to minimize losses due to interference with code C032. So, the machine can be refilled repeatedly without interruption, as well as adding error information via SMS using an Arduino microcontroller. Method was used experimental of placement sensor modification of photo interrupter and ATDC (After Top Dead Center) sensor. The results showed that after modifying the sensor placement, the number of refills could be increased to an average usage of toner exceeding 12 refills before the error code C032 occurred. This was because of the opto sensor was covered by toner powder and with an indicator that controlled the toner rotation it had reached set point. Then, with SIM 800L, which sends SMS and miss call notifications to users with a success rate of 98% and 2% error. Therefore, it helps users of the Minolta Bizhub 421 photocopier can more easily supervise the toner tube.